Water deprivation induces hypoactivity in rats independently of oxytocin receptor signaling at the central amygdala - Felintro, Viviane; Trujillo, Verónica; dos-Santos, Raoni C.; da Silva-Almeida, Claudio; Reis, Luís C.; Rocha, Fábio F.; Mecawi, André S. (Frontiers in Endocrinology, 2023)
Vasopressin (AVP) and oxytocin (OXT) are neuropeptides produced by magnocellular neurons (MCNs) of the hypothalamus and secreted through neurohypophysis to defend mammals against dehydration. It was recently demonstrated that MCNs also project to limbic structures, modulating several behavioral responses. We found that 24 h of water deprivation (WD) or salt loading (SL) did not change exploration or anxiety-like behaviors in the elevated plus maze (EPM) test. However, rats deprived of water for 48 h showed reduced exploration of open field and the closed arms of EPM, indicating hypoactivity during night time. We evaluated mRNA expression of glutamate decarboxylase 1 (Gad1), vesicular glutamate transporter 2 (Slc17a6), AVP (Avpr1a) and OXT (Oxtr) receptors in the lateral habenula (LHb), basolateral (BLA) and central (CeA) amygdala after 48 h of WD or SL. WD, but not SL, increased Oxtr mRNA expression in the CeA. Bilateral pharmacological inhibition of OXTR function in the CeA with the OXTR antagonist L-371,257 was performed to evaluate its possible role in regulating the EPM exploration or water intake induced by WD. The blockade of OXTR in the CeA did not reverse the hypoactivity response in the EPM, nor did it change water intake induced in 48-h water-deprived rats. In conclusion, we found that WD modulates exploratory activity in rats, but this response is not mediated by oxytocin receptor signaling to the CeA, despite the upregulated Oxtr mRNA expression in that structure after WD for 48 h.